Does the “last chance” sentence work?: ten years of failures and successes under a juvenile intermediate sanction in Canada - Fortin-Dufour, Isabelle (Punishment & society, 2018)
Deferred custody and supervision order, an intermediate sanction which came into effect in 2003, had never been the subject of a scientific study. In the absence of research data, judges would give the sentence without knowing the outcome. To fill this gap, this study presents the failure rates (technical violations, revocations and new-crime violations) and success rates of all young Quebecers who completed a deferred custody and supervision order between 1 June 2003 and 31 May 2012. As with studies that examined similar sentences elsewhere in the world, success rates are relatively low. Suggestions are made to limit failures associated with this type of juvenile intermediate sanctions.